2020
DOI: 10.1080/13691058.2020.1718758
|View full text |Cite
|
Sign up to set email alerts
|

How do women and girls experience menstrual health interventions in low- and middle-income countries? Insights from a systematic review and qualitative metasynthesis

Abstract: Increasing recognition of the difficulties women and adolescent girls face during menstruation has the prompted rapid implementation of menstrual health programmes and policies. Yet, there remains limited understanding of the influence of these interventions on individuals' menstrual experiences. We systematically reviewed and synthesised qualitative studies of participant experiences of menstrual health interventions. Included studies were undertaken in 6 countries (India, Uganda, Kenya, Ethiopia, Zimbabwe, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 24 publications
1
31
0
1
Order By: Relevance
“…It is plausible that experiences and learnt expectations from home environments influence perceptions of school environments. Changes to individuals’ expectations for their menstrual experience in response to interventions were an overarching theme of a recent meta-synthesis of qualitative studies of menstrual health interventions and would fit with this interpretation of our findings 41. Alternatively, a joint predictor, such as internalised stigma, may contribute to both appraisals.…”
Section: Discussionsupporting
confidence: 67%
“…It is plausible that experiences and learnt expectations from home environments influence perceptions of school environments. Changes to individuals’ expectations for their menstrual experience in response to interventions were an overarching theme of a recent meta-synthesis of qualitative studies of menstrual health interventions and would fit with this interpretation of our findings 41. Alternatively, a joint predictor, such as internalised stigma, may contribute to both appraisals.…”
Section: Discussionsupporting
confidence: 67%
“…Changes to individuals' expectations for their menstrual experience in response to interventions was an overarching theme of a recent meta-synthesis of qualitative studies of menstrual health interventions and would fit with this interpretation of our findings. [36] Alternatively, a joint predictor, such as internalised stigma, may contribute to both appraisals. This should be explored in future research and may indicate the need to assess both location responses even if interventions only focus on school infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…Progress has been made against the research needs that were identified. Overall, support from global funding bodies and research councils has increased, facilitating research beyond qualitative and descriptive studies [20] to include cross-sectional studies in Bangladesh [21], pilot intervention trials in Kenya, Uganda and the Gambia including varying combinations of WASH, sexual and reproductive health (SRH) and education [23], intervention studies in Bangladesh and Uganda [24,25]; full intervention trials in Kenya, and systematic reviews with meta-analyzes analyzing MHM-related evidence and measures and outcomes being utilized [1,9,10,[26][27][28][29]. In Kenya and the Philippines (see Boxes 2 and 3), evidence has fed directly into national policy and monitoring efforts influencing both countries' education systems.…”
Section: Update Of Progess Since 2014mentioning
confidence: 99%